THE UTILIZATION OF MOBILE-HEALTH INTERVENTION IN IMPROVING TREATMENT COMPLIANCE BEHAVIOR IN TUBERCULOSIS PATIENTS - Eko Budi Laksono; Andrew Johan; Meira Erawati (Nurse and Health, 2022)
Background: Mobile-health assists health workers in monitoring and observing patient compliance behavior during TB treatment.